Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,=\dfrac{13}{50}\cdot\dfrac{50}{13}\cdot\left(-\dfrac{31}{2}\right)\cdot\dfrac{169}{2}=-\dfrac{5239}{2}\\ b,=\dfrac{-\dfrac{49}{100}\cdot\left(-125\right)}{-\dfrac{343}{27}\cdot\dfrac{81}{16}\cdot\left(-1\right)}=\dfrac{\dfrac{245}{4}}{\dfrac{1029}{16}}=\dfrac{245}{4}\cdot\dfrac{16}{1029}=\dfrac{20}{21}\)
a) \(\dfrac{13}{50}.\left(-15.5\right):\dfrac{13}{50}.84\dfrac{1}{2}=\dfrac{13}{50}.-75:\dfrac{13}{50}.\dfrac{169}{2}=-\dfrac{75.169}{2}=-\dfrac{12675}{2}\)
b) \(\dfrac{\left(-0,7\right)^2.\left(-5\right)^3}{\left(-2\dfrac{1}{3}\right)^3.\left(1\dfrac{1}{2}\right)^4.\left(-1\right)^5}=\dfrac{0,49.\left(-125\right)}{-\dfrac{343}{27}.\dfrac{81}{16}.\left(-1\right)}=-\dfrac{\dfrac{245}{4}}{\dfrac{1029}{16}}=\dfrac{20}{21}\)
\(2\times\left(x-\frac{1}{7}\right)=0\)
\(x-\frac{1}{7}=0:2=0\)
\(x=0+\frac{1}{7}\)
\(x=\frac{1}{7}\)
vậy \(x=\frac{1}{7}\)
\(\frac{x}{-4}=\frac{-3}{5}\)
\(\Leftrightarrow5x=-3.\left(-4\right)=12\)
\(x=\frac{12}{5}\)
vậy \(x=\frac{12}{5}\)
\(\frac{2,1}{0,7}=\frac{x}{3}\)
\(\Leftrightarrow2,1.3=0,7x\)
\(6,3=0,7x\)
\(x=6,3:0,7\)
\(x=9\)
vậy \(x=9\)
a) 2x(x - 1/7) = 0 b) x/-4 = -3/5 c) 2,1/0,7 = x/3
TH1: 2x = 0 => x = 0 x = -3/5 x 4 2,1 . 3 = 0,7 . x
TH2: x -1/7 = 0 => x = 0 + 1/7 => x = 1/7 x = -12/5 6,3 = 0,7 . x
x = 6,3 : 0, 7
x = 9
\(\frac{x-1}{-15}=\frac{-60}{x-1}\)
\(\Leftrightarrow\left(x-1\right)^2=900\\ \Leftrightarrow\left(x-1\right)^2=\left(\pm30\right)^2\\ \Rightarrow x-1\in\left\{30;-30\right\}\)
\(\Rightarrow\left[{}\begin{matrix}x-1=30\\x-1=-30\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=31\\x=-29\end{matrix}\right.\)
Vậy...
Mk giải câu 1 nha
1) 2x - 3 = x + 1/2
➡️2x - x = 1/2 + 3
➡️x = 7/2
Hok tốt~
\(3\left(x-2\right)-4\left(2x+1\right)-5\left(2x+3\right)=50\)
<=>\(3x-6-8x-4-10x-15=50\)
<=>\(-15x-25=50\)
<=>\(-15x=75\)
<=>\(x=-5\)
\(3\left(x-2\right)-4\left(2x+1\right)-5\left(2x+3\right)=50\)
\(\Rightarrow3x-6-8x-4-10x-15=50\)
\(\Rightarrow3x-8x-10x=50+6+4+15\)
\(\Rightarrow3x-8x-10x=75\)
\(\Rightarrow x\left(3-8-10\right)=75\)
\(\Rightarrow x.\left(-15\right)=75\)
\(\Rightarrow x=75:\left(-15\right)\)
\(\Rightarrow x=-5\)
\(\text{Vậy }x=-5\)
Ta có:3(x-2) - 4(2x+1) - 5(2x+3)=50
=>3x-6-8x-4-10x-15=50
=>-15x-25=50
=>-15x=75
=>x=-5
Vậy x=-5
2x - \(\dfrac{1}{2}-\dfrac{1}{6}-...-\dfrac{1}{49.50}\)= 6-\(\dfrac{1}{50}\) + x
<=> x - ( \(\dfrac{1}{1.2}+\dfrac{1}{2.3}+...+\dfrac{1}{49.50}\)) = \(\dfrac{299}{50}\)
<=> x - \(\left(1-\dfrac{1}{50}\right)\) = \(\dfrac{299}{50}\)
<=> x - \(\dfrac{49}{50}\) = \(\dfrac{299}{50}\)
<=> x = \(\dfrac{174}{25}\)
\(2x-\dfrac{1}{2}-\dfrac{1}{6}-\dfrac{1}{12}-...-\dfrac{1}{49\cdot50}=7-\dfrac{1}{50}+x\)
\(\Leftrightarrow2x-\left(1-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+...+\dfrac{1}{49}-\dfrac{1}{50}\right)=x+\dfrac{349}{50}\)
\(\Leftrightarrow2x-\dfrac{49}{50}-x-\dfrac{349}{50}=0\)
=>x=398/50=199/25
ủa bn cũng trl linh tinh mà?!
\(\frac{50%}{0,7}=\frac{-2}{2x+1}\)
\(\Rightarrow\frac{5}{7}=\frac{-2}{2x+1}\)
=> 5 . ( 2x + 1 ) = -2 . 7
=> 10x + 1 = -14
=> 10x = -15
=> x = -1,5
Vậy x = -1,5